Technology-enhanced practice competencies: scoping review and novel model development - Perle, Jonathan G.; Chandran, Dilip N.; Brezler, Emily; Coleman, Michelle; Deziel, Julia; Nahhas, Patrick; McDonald, Gabrielle; Jent, Jason F. (Frontiers in Digital Health, 2025)
IntroductionWith technology routinely integrated into healthcare, it is essential that practitioners obtain skills in the numerous competencies required. Unfortunately, literature to guide use remains inconsistent and fragmented. The current scoping review identified technology-enhanced practice competencies for healthcare practitioners among peer-reviewed literature.MethodsA review of PubMed, Scopus, Web of Science, PsycInfo, Global Index Medicus, and Journal of Technology in Behavioral Science was conducted between November 2022 and March 2023.Results10,583,799 articles were identified, with 109 included in the final review. Seventeen primary competencies were identified with ethics (77.1%), legality (68.8%), and data security (65.1%) among the top three.ConclusionsAlthough multiple technologies across specialties were identified, limited literature comprehensively defined technology-enhanced practice competencies to guide practitioner education. To address this gap, the Intersectional Technology Education and Competency in Healthcare (iTECH) Model was created to clarify educational targets for the use of technology in healthcare practices. Model development and finding applications are discussed.